2022
DOI: 10.3892/or.2022.8300
|View full text |Cite
|
Sign up to set email alerts
|

Levels of circulating mast cell progenitors and tumour‑infiltrating mast cells in patients with colorectal cancer

Abstract: The role of mast cells in colorectal cancer (CRC) has been an area of intense interest. Mast cell density is closely related to CRC development and prognosis. The identification of mast cell progenitors (MCps) in peripheral blood provides an opportunity to explore the frequency and distribution of mast cells in the circulation and tumour microenvironment of patients with CRC at different disease stages. The aim of the presents study was to investigate the changes of MCps and mast cells in CRC. Flow cytometry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Many researchers have investigated the correlation between MCs and CRC patient prognosis ( Table 1 ). Some authors believe that MCs are correlated with a good prognosis ( 22 , 117 , 118 ), while others believe that mast cells are not associated with prognosis ( 59 , 119 , 120 ), but most studies suggest that mast cells are associated with reduced survival rates ( 2 , 121 123 ).…”
Section: Mast Cells and Prognosis In Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have investigated the correlation between MCs and CRC patient prognosis ( Table 1 ). Some authors believe that MCs are correlated with a good prognosis ( 22 , 117 , 118 ), while others believe that mast cells are not associated with prognosis ( 59 , 119 , 120 ), but most studies suggest that mast cells are associated with reduced survival rates ( 2 , 121 123 ).…”
Section: Mast Cells and Prognosis In Crcmentioning
confidence: 99%
“…Zhao et al. ( 120 ) reported that circulating mast progenitor cell (MCp) levels are low in CRC patients and are significantly associated with CRC progression, and the frequency of MCps may be an independent indicator of the aggressiveness of CRC in patients and may be used to distinguish between patients with early and advanced CRC. However, mast cells in tumour tissue are not associated with CRC progression.…”
Section: Mast Cells and Prognosis In Crcmentioning
confidence: 99%
“…Previous studies have revealed that mast cells had proor anti-tumorigenic roles depending on the tumor types, the stage, and localization within the tumor. Activated mast cells have been shown to be associated with poor prognosis in thyroid cancer (38), gastric cancer (39), hepatic cellular carcinoma (40), and colorectal cancer (41). Mast cell density is increased in gastric cancer, and correlated with angiogenesis, the number of metastatic lymph nodes, and patient survival (42).…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhao et al, a lower frequency of circulating MCs and their progenitors was found in patients with CRC than in healthy patients; this was especially apparent in patients with advanced disease. It turned out that this may reflect aggressive CRC course ( 99 ).…”
Section: The Role Of the Immune System In The Prognosis And Treatment...mentioning
confidence: 99%